2016
DOI: 10.3897/zookeys.552.6039
|View full text |Cite
|
Sign up to set email alerts
|

Further contributions to the longhorn beetle (Coleoptera, Cerambycidae) fauna of New Brunswick and Nova Scotia, Canada

Abstract: Sixteen species of Cerambycidae are newly recorded for New Brunswick, Canada; Arhopalus obsoletus (Randall), Atimia confusa confusa (Say), Callidium frigidum Casey, Phymatodes amoenus (Say), Phymatodes testaceus (Linnaeus), Neoclytus mucronatus mucronatus (Fabricius), Xylotrechus aceris Fisher, Xylotrechus sagittatus sagittatus (Germar), Tylonotus bimaculatus Haldeman, Lepturges angulatus (LeConte), Lepturges symmetricus (Haldeman), Urgleptes querci (Fitch), Oplosia nubila (LeConte), Eupogonius subarmatus (LeC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Traps placed in the middle or high canopy of oak trees captured more N. raddei than those placed in the understorey, indicating that canopy traps would be more efficacious for surveys and mass trapping than understorey traps. Previous studies have found that the species composition of longhorn beetles in traps differs between the forest canopy and the understorey (Graham et al, 2012;Dodds, 2014;Webster et al, 2016). Feeding habits of larvae and adults may influence whether beetles were captured in canopy or understorey traps.…”
Section: Discussionmentioning
confidence: 99%
“…Traps placed in the middle or high canopy of oak trees captured more N. raddei than those placed in the understorey, indicating that canopy traps would be more efficacious for surveys and mass trapping than understorey traps. Previous studies have found that the species composition of longhorn beetles in traps differs between the forest canopy and the understorey (Graham et al, 2012;Dodds, 2014;Webster et al, 2016). Feeding habits of larvae and adults may influence whether beetles were captured in canopy or understorey traps.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on attractants were not collected for non-target species. See Webster et al (2012r), Hughes et al (2014), and Webster et al (2016) for additional details of the lures and methods used to deploy Lindgren traps and collect samples. A description of the habitat was recorded for all specimens collected during this survey.…”
Section: Methods and Conventionsmentioning
confidence: 99%
“…Recently, Pelletier and Hébert (2014) reviewed the Cantharidae of eastern Canada and reported 19 species new to New Brunswick. Most recently, Webster et al (2016) newly reported an additional 16 species of Cerambycidae for the province. These baseline biodiversity data are important for documentation of changes in our ecosystems due to human intervention and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Traps were baited with various combinations of lures for detecting Cerambycidae. See Webster et al (2012b), Hughes et al (2014), and Webster et al (2016a) for details of the lures and methods used to deploy Lindgren traps and collect samples. A description of the habitat was recorded for all specimens collected during this survey.…”
Section: Methods and Conventionsmentioning
confidence: 99%